2020
DOI: 10.1038/s41598-020-73237-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of FDG-PET radiomics with machine learning in pancreatic cancer

Abstract: Patients with pancreatic cancer have a poor prognosis, therefore identifying particular tumor characteristics associated with prognosis is important. This study aims to investigate the utility of radiomics with machine learning using 18F-fluorodeoxyglucose (FDG)-PET in patients with pancreatic cancer. We enrolled 161 patients with pancreatic cancer underwent pretreatment FDG-PET/CT. The area of the primary tumor was semi-automatically contoured with a threshold of 40% of the maximum standardized uptake value, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 29 publications
0
54
0
1
Order By: Relevance
“…The GLNU increases with the tumor heterogeneity, which is related to tumor invasion, treatment response and prognosis (76). As an independent risk factor for poor prognosis, high GLNU is associated with worse survival in patients with pancreatic cancer who have undergone surgery (72). Our study showed that tumors with LVI had higher GLNU values than those without LVI, while the presence of LVI implies an increase in tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The GLNU increases with the tumor heterogeneity, which is related to tumor invasion, treatment response and prognosis (76). As an independent risk factor for poor prognosis, high GLNU is associated with worse survival in patients with pancreatic cancer who have undergone surgery (72). Our study showed that tumors with LVI had higher GLNU values than those without LVI, while the presence of LVI implies an increase in tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 55%
“…In our study, GLNU was another independent predictor for LVI. Gray-level non-uniformity (GLNU) is a measure of the similarity of gray-level values throughout the image (72). Many radiomics features are unstable in different reconstruction algorithms, while GLNU is one of the most repetitive radiomics features showing good stability (73).…”
Section: Discussionmentioning
confidence: 99%
“…We collected 47 publications on “Other” cancer types. This category included studies on gastrointestinal (11) [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 ], pancreatic (8) [ 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 ], sarcoma (8) [ 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 ], neuroendocrine (5) [ 284 , 285 , 286 , 287 , 288 ], prostate (4) [ 289 , 290 , 291 , 292 ], thyroid (3) [ 293 , 294 , 295 ], thymic (2) [ 296 , 297 ], skin (2) [ 298 , 299 ], liver (2) [ 300 , 301 ], and renal carcinomas (1) [ 302 ]. The average number of patients was 84 (median = 70, range, 26–214) and the average number of textural features extracted was 29 (median = 17, ...…”
Section: Resultsmentioning
confidence: 99%
“…Compared with most previous texture analysis studies in PDAC that were based on CT imaging [ 15 17 , 39 , 40 ], we performed radiomics analysis based on MRI, which has a higher resolution in soft tissue than CT. Although based on different examination techniques, the selected features are mostly related to intratumoural heterogeneity [ 32 , 37 , 38 ]. However, performances have not yet been compared among CT, MRI, and PET/CT [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%